Penerapan Metode Multi Attribute Utility Theory Pada Sistem Pendukung Keputusan Seleksi Bantuan Untuk Madrasah - Abdul Malik I Buna; Citra Yustitya Gobel; Zufrianto Dunggio; Deya Riski Haluti (STMIK Budi Darma, 2022)
Madrasah is one form of religious education that has contributed greatly to the development of the nation. Through madrasas, they are able to give birth to a generation of Islamic character and national insight, but the selection process for madrasa aid recipients in the city of Gorontalo is currently not optimal in terms of determining madrasa aid recipients, this occurs due to inaccuracies between recipient data and existing requirements, the selection process for recipients of assistance requires a long time, lack of accuracy between the criteria and requirements of the beneficiary so that it is vulnerable to manipulation. The research objective is to design a Madrasah Assistance Selection Decision Support System applying the Website-Based Multi-Attribute Utility Theory Method so that the selection process for providing madrasah operational assistance can be carried out optimally and measurably using decision-making methods so that it is expected to determine more precise selection results. This study uses whitebox and blackbox testing. Whitebox testing is testing with testing techniques on program flow, logical structure and program procedures by mapping flowcharts, then calculating the number of edges and nodes. The black box testing method focuses on the functional importance of the software. Therefore, blackbox testing allows software developers to create a set of input conditions that will train all functional requirements of a program whether it runs as expected or vice versa. Based on the results of whitebox testing on one of the processes in this system, namely the value data module with balanced results, namely Cyclomatic Complexity (CC) = 4, then this system is declared to be running well. While the results of the blackbox test system can run as expected and efficient